Understanding and Addressing Bullying Behavior in Children - Bakhtawar Siddique; Dr. Waleed Khan; Dr Umara Rauf (Al Manhal Research Journal, 2024)
Bullying among children has emerged as a significant societal concern, impacting the mental and emotional well-being of victims. This comprehensive review aims to provide an in-depth understanding of bullying behavior in children, including its definition, prevalence, contributing factors, consequences, and interventions. Drawing upon a wide range of research studies and scholarly articles, this review explores various dimensions of bullying, including its forms (e.g., physical, verbal, relational, cyber bullying), developmental trajectories, and the role of individual, familial, and societal factors in its occurrence. Additionally, this review highlights the detrimental effects of bullying on victims, perpetrators, and bystanders, emphasizing the need for proactive intervention strategies. Finally, evidence-based interventions and prevention programs are discussed, offering insights into effective approaches for addressing bullying behavior and fostering positive social relationships among children.